2021
DOI: 10.1109/access.2021.3118044
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Variations in Grass C. dactylon and Selection of Optimal LEDs for the Horticulture Luminaire Using LM Algorithm

Abstract: Healing of various ailments using herbal medicines is gaining much interest. Plants classified as grasses, specifically Cynodon dactylon, are an appreciated group of monocots used in many herbal remedies. In this work, C. dactylon, is grown naturally and also under market available LED Luminaires with different lighting conditions. Until 2010, most of the plants were grown under conventional lamps that are not spectrally tunable. Cynodon dactylon, the grass, was grown under two different light spectrum, two li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The studies in [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], and [29] demonstrate how dynamic lighting and optimization methods can help to increase the energy savings achievable by LED systems. In [17], the effects of dynamic regulation of supplemental lighting intensity on electricity consumption and fresh weight buildup were examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies in [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], and [29] demonstrate how dynamic lighting and optimization methods can help to increase the energy savings achievable by LED systems. In [17], the effects of dynamic regulation of supplemental lighting intensity on electricity consumption and fresh weight buildup were examined.…”
Section: Introductionmentioning
confidence: 99%
“…In [27], a herbal remedy plant was grown under natural light and under LED fixtures with varying light conditions. Simulation of multiple spectra showed that the method could replicate the intended spectrum with minimum fitness errors.…”
Section: Introductionmentioning
confidence: 99%